A critical analysis on African Traditional Religion and the Trinity - Manganyi, Jele S. (HTS teologiese studies, 2013)
To what extent do the resources of African Traditional Religion (ATR) contribute towards Christian theological discourse and benefit the African church? ATR is accommodated in the African Initiated Churches (AICs). The members of these churches aim to be Christian without losing their African identity. ATR is a religion that was practised throughout Africa before the arrival of the Western missionaries. The core premise of ATR is the maintenance of African culture and its main feature is loyalty to the ancestors and the accompanying rituals that express this loyalty. This study addresses the appropriateness of ATR’s resources in terms of their contribution to the doctrine of the Trinity. When the early church worshipped God the Father and God the Son (Jesus) in the presence of the Holy Spirit, a tension developed. The questions of monotheism versus polytheism and the nature and position of Jesus within the Trinity were put forward and addressed. The doctrine of the Trinity is uniquely Christian and includes the belief in Jesus Christ as the Son of God who alone mediates between God and men. There is, on the other hand, an understanding that Africans worship one Supreme Being and venerate ancestors as intermediaries to the one Supreme Being, without clear roles being ascribed to Jesus Christ and the Holy Spirit. This article enquires whether the process of Africanisation and contextualisation consciously or unconsciously downgraded Jesus Christ as Mediator who came to reveal who God is and to reconcile humankind to him.